Propriedades estruturais e eletrônicas de nanopartículas de Cu modificam a estrutura superficial do cobre e influenciam na atividade catalítica para a reação deslocamento gás água - Caldas, Paula Cristina de Paula (2017)
The Cu catalysts activity is modified by reducible supports, such as cerium and praseodymium oxides. The interaction of these oxides with Cu nanoparticles prevent agglomeration and generate active interface sites. The relationship between structure and reaction velocity have been calculated from model catalysts that have properties very far from a real catalyst. One of the great challenges is the understanding of ceria and praseodymia effects on the modification of the properties of copper catalytic sites. The activity - structure relationship during the water gas reaction for supported copper catalysts in interaction with cerium or praseodymium oxides or not was investigated on this study. Through in situ studies, it was found that for the Cu/Al2O3 catalysts the growth of the metal particle, caused by the increase of the Cu content supported in the alumina, led to a decrease in the oxygen coating degree. Which, in turn, generated an increase on the surface electron density of the particle resulting in the elongation of the Cu-O surface bonding distance. When different ceria or praseodymia contents were added to the Cu/Al2O3 catalysts did not cause significant changes in particle size and the oxidation state of copper. However, the oxide-metal interaction resulted in an increase on the surface electron density of the copper particle causing an increase in the Cu-O bond distance over the non-promoted catalysts. A linear correlation between Cu-O binding distance and catalytic activity for WGSR is observed. Therefore, Cu-O bonding distance reflects the electronic properties and activity of copper sites.